Conceptualization of the Holobiont Paradigm as It Pertains to Corals - Goulet, Tamar L.; Erill, Ivan; Ascunce, Marina S.; Finley, Sheree J.; Javan, Gulnaz T. (Frontiers in Physiology, 2020)
Corals’ obligate association with unicellular dinoflagellates, family Symbiodiniaceae form the foundation of coral reefs. For nearly a century, researchers have delved into understanding the coral-algal mutualism from multiple levels of resolution and perspectives, and the questions and scope have evolved with each iteration of new techniques. Advances in genetic technologies not only aided in distinguishing between the multitude of Symbiodiniaceae but also illuminated the existence and diversity of other organisms constituting the coral microbiome. The coral therefore is a meta-organism, often referred to as the coral holobiont. In this review, we address the importance of including a holistic perspective to understanding the coral holobiont. We also discuss the ramifications of how different genotypic combinations of the coral consortium affect the holobiont entity. We highlight the paucity of data on most of the coral microbiome. Using Symbiodiniaceae data, we present evidence that the holobiont properties are not necessarily the sum of its parts. We then discuss the consequences of the holobiont attributes to the fitness of the holobiont and the myriad of organisms that contribute to it. Considering the complexity of host-symbiont genotypic combinations will aid in our understanding of coral resilience, robustness, acclimation and/or adaptation in the face of environmental change and increasing perturbations.